Turbo modulation and coding: design and evaluation of iterative bit-interleaved coded modulation methods for wireless systems beyond 3G - Bauch, Gerhard; Schreckenbach, Frank; Hausl, Christoph; Abe, Tetsushi (European transactions on telecommunications, 2007)
We give an overview of iterative techniques for bit‐interleaved coded modulation. We start with simple methods where a convolutional code is concatenated with a standard QAM modulation scheme. The mapping is carefully chosen different from Gray mapping such that significant gains can be obtained by an iterative (turbo) receiver. The idea can also be applied to transmit antenna diversity as well as spatial multiplexing (MIMO). We then consider various powerful iterative coding schemes which are under discussion in standardisation for wireless systems beyond 3G such as serial or parallel concatenated convolutional codes, repeat accumulate codes and LDPC codes. We give a comparison in terms of complexity and performance.The main intention is to provide an illustrative overview over relevant applications of the turbo principle in demodulation and decoding. It is a summary of results which have been obtained in collaboration between the Institute of Communications Engineering, TUM and DoCoMo Euro‐Labs. Copyright © 2007 John Wiley & Sons, Ltd.